Outdoor gyms in Santiago: urban distribution and effects on physical activity - Rodrigo Mora; Gerard Weisstaub; Margarita Greene; Geraldine Herrmann (Universidade Estadual Paulista (UNESP), 2017)
Abstract Aims To put together a registry of the location of all existing outdoor gyms (OGs) in Santiago, Chile, and establish a profile of the users of these gyms. Methods All OGs in Santiago located in public spaces were identified and geo-referenced, and an accessibility analysis of them was carried out. A total of 1,023 users of OGs were surveyed (71% men, average age 31.5 years old, SD =16.6), about the frequency of use of OGs, amount of time spent using them, transportation habits, motivation for usage, and their perceptions regarding their own health, among other questions. In addition, each person's neck circumference was measured. Results There are 1,981 OGs in the city squares, sidewalks and parks, mostly located in poorest areas of the city. Most OG users live less than one kilometer away from an OG. Discussion In line with international studies, this research demonstrates that OGs have positive collateral effects, as they not only contribute to users to increase their physical activity, but also because they attract people with sedentary lifestyles to make physical activity. This, in turn, might contribute to make urban areas more livable and safer, for they bring new "eyes to the street" and permit to use cities' under-occupied public spaces. Conclusion The proliferation of outdoor gyms should be regarded as an opportunity for public health policies aimed at tackling the obesity problem and increasing the physical activity of people.